Development of electrical resistance tomography applying vertical metallic column - Suzanna, Ridzuan Aw; Ruzairi, Hj Abd Rahim; Yasmin, Abdul Wahab; Farah Hanan, Azimi; Lia Safiyah, Syafie; Raja Siti Nur Adiimah, Raja Aris (IOP Publishing, 2021)
Majority of industrial pipelines and process vessels are constructed from conducting composites. This paper focusing on the hardware and software development of laboratory test Electrical Resistance Tomography (ERT) measurement methods to obtain the cross-sectional image of the conductivity distribution of gas bubble phantom in a static vertical metallic column filled with water. The system with sixteen sensors implementation was investigated on a stainless steel vertical column of 100 mm inner diameter. The conducting boundary strategy was applied as the measurement strategy. Software for the current study was developed using Graphical User Interface (GUI) application program in MATLAB. The software contains many functions to ease user to get necessary information from the research done. The cross section image of the bubble phantom was reconstructed using Linear Back Projection (LBP) algorithm after the data collection process was completed. The system has been tested and can successfully generate the phantom under test.